Why Have College Completion Rates Increased? - Jeffrey T. Denning; Eric R. Eide; Merrill Warnick (Institute of Labor Economics (IZA), 2019)
College completion rates declined from the 1970s to the 1990s. We document that this trend has reversed - since the 1990s, college completion rates have increased. We investigate the reasons for the increase in college graduation rates. Collectively, student characteristics, institutional resources, and institution attended do not explain much of the change. However, we document that standards for degree receipt may explain some of the change in graduation rates.
Keywords: I23; I21; 330; college completion